2024
DOI: 10.1186/s12879-023-08964-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and seroprevalence of Toxoplasma gondii in COVID‑19 patients; a first case-control study in Iran

Mehdi Hasanzadeh,
Ehsan Ahmadpour,
Mahmoud Mahami-Oskouei
et al.

Abstract: Background Toxoplasmosis is a serious or life-threatening disease in immunosuppressed patients and pregnant women. This study examined the likely association between Toxoplasma gondii infection and COVID-19 patients with moderate illness. Methods Seventy blood samples were collected from patients at the Health Reference Laboratory of Tabriz, Northwest Iran from April 2021 to September 2021. In addition, 70 healthy subjects of the same age (37 ± 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…et al in Mexico revealed that 21.9% of patients with COVID-19 showed the presence of T. gondii (17). Studies by Gouda MA, et al, (20) and Hasanzadeh M, et al (22) indicated the absence of active T. gondii infection in patients with COVID-19 by IgM detection.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…et al in Mexico revealed that 21.9% of patients with COVID-19 showed the presence of T. gondii (17). Studies by Gouda MA, et al, (20) and Hasanzadeh M, et al (22) indicated the absence of active T. gondii infection in patients with COVID-19 by IgM detection.…”
Section: Discussionmentioning
confidence: 97%
“…The frequency of exposure to T. gondii, detected through the presence of IgG in patients with COVID-19, reached 49% (95% CI: 34-63%; 2,947 participants; 13 studies; I 2 = 98%, p < 0.01) (Fig. 2) (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In addition, the frequency of exposure to T. gondii, detected through the presence of IgM in patients with COVID-19, reached 2% (95% CI: 0-6%; 1,302 participants; 6 studies; I 2 = 94%, p < 0.01) (Fig.…”
Section: Quality Of the Included Studies And Publication Biasmentioning
confidence: 98%
See 3 more Smart Citations